CURRENT STATUS OF ADMINISTRATIVE AND LEGAL PROTECTION OF AREAS WITH SPECIAL CONDITIONS FOR MILITARY FACILITY USE - Komar, Andrii (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . Administrative and legal protection of land around military facilities located in areas with special conditions of use is an important tool for ensuring national security, especially during martial law. Establishing an adequate legal regime in such areas is crucial for the effective functioning of defense facilities and for protecting citizens’ lives and the environment. However, the existing regulatory and legal acts in Ukraine do not provide a sufficient level of protection for such territories. This necessitates an analysis of the current legislation, the practice of its application, the activities of executive authorities and local self-government bodies, as well as the improvement of control mechanisms and administrative liability. M e t h o d s . General scientific methods of analysis and synthesis, as well as formal legal methods, were used. These made it possible to study the content of legal norms, identify practical problems, generalize practical aspects, and formulate proposals for improving legal regulation. R e s u l t s . The legal nature of the administrative and legal protection of lands with special conditions of use around military facilities was studied. It was established that Ukraine lacks a special law defining the legal regime, boundaries, and land use rules in such areas. A number of administrative and procedural dysfunctions were identified, including: the absence of proper legal regulation of areas with special conditions of use of military facilities; the lack of integration of data on legal restrictions on land use around military facilities in the State Land Cadastre; the absance of an effective mechanism for interagency coordination between executive authorities, local self-government bodies, and military formations; and the low level of utilization of public control potential. The need to develop a special draft law that defines the legal regime for territories around military facilities, unifies transparency, predictability, and accountability for the protection of such lands has been substantiated. C o n c l u s i o n s . The current state of administrative and legal protection of zones with special conditions of use around military facilities is at an early stage of development and requires further improvement. The necessary steps include: legislative regulation of the procedure for determining and establishing zones with special use regimes (as a type of zone with special conditions of use) around military facilities; improvement of interagency cooperation procedures and the inclusion of information in the State Land Cadastre; establishment of administrative liability for violations of the legal regime of such territories; active introduction of modern means of control (monitoring) of land resources; involvement of the public in the process of land protection.